Large-eddy simulations of flow and heat transfer for jet impingement on static and vibrating surfaces - Natarajan, Thangam (Curtin University, 2017)
The present numerical work serves to understand the flow and thermal characteristics of a turbulent impinging air jet under dynamic flow and geometric conditions using Large-eddy Simulations (LES). A clear relationship between the large-scale structures and resulting heat transfer on the impingement surface exists and was demonstrated through highly-resolved LES of both static and dynamic surface configurations.